2017
DOI: 10.18632/oncotarget.18271
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor-binding site variants affect prostate cancer progression

Abstract: Vitamin D is an important modulator of cellular proliferation through the vitamin D receptor (VDR) that binds to DNA in the regulatory sequences of target genes. We hypothesized that single nucleotide polymorphisms (SNPs) in VDR-binding sites might affect target gene expression and influence the progression of prostate cancer. Using a genome-wide prediction database, 62 SNPs in VDR-binding sites were selected for genotyping in 515 prostate cancer patients and the findings were replicated in an independent coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Numerous epidemiological studies have shown the association between the amount of dietary vitamin D, vitamin D level in circulation, and sunlight exposure with prostate cancer risk [71]. In addition, genetic polymorphisms in VDR were associated with prostate cancer susceptibility and prostate cancer progression [72,73,74]. VDR-knockout mice showed higher cell proliferation than wild-type mice [75].…”
Section: Subfamilies Of Nrsmentioning
confidence: 99%
“…Numerous epidemiological studies have shown the association between the amount of dietary vitamin D, vitamin D level in circulation, and sunlight exposure with prostate cancer risk [71]. In addition, genetic polymorphisms in VDR were associated with prostate cancer susceptibility and prostate cancer progression [72,73,74]. VDR-knockout mice showed higher cell proliferation than wild-type mice [75].…”
Section: Subfamilies Of Nrsmentioning
confidence: 99%
“…Low expression of TUSC-3 was shown to correspond with poor PCa prognosis in patients, and TUSC-3 silencing enhanced cell migration and growth. 62 However, 1,25-Vitamin D strongly induced the expression of TUSC-3 in PCa cells. In a Phase II clinical trial, PCa patients with the highest serum levels of prostatic 1,25(OH)2D also had low COX-2 levels, but exhibited high IL-6 levels in their stroma tissue.…”
Section: Introductionmentioning
confidence: 97%
“… 51 , 53 , 62 , 63 In Taiwanese PCa patients, genetic variants, HFE rs9393682, and TUSC-3 rs1378033 were associated with time to progression in localized disease and low risk of advanced PCa for patients undergoing androgen deprivation therapy. 62 Furthermore, in vitro studies revealed 1,25-Vitamin D downregulated HFE and when silenced HFE impedes cell proliferation and wound healing. Low expression of TUSC-3 was shown to correspond with poor PCa prognosis in patients, and TUSC-3 silencing enhanced cell migration and growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a non-coding single-stranded RNA, miRNA affects the biological functions of cells through its complete or incomplete complementary binding to the 3'-end of target genes (4,5). miR-129 is a miRNA located in the genomic region near the fragile site of chromosome 7q (6), and fragile site loss is closely related to the malignancy of prostate cancer (7). miR-129-3p is a miRNA closely correlated with the development and progression of tumors and the expression is low in gastric cancer (8) and breast cancer (9), functioning as a tumor suppressor gene.…”
Section: Introductionmentioning
confidence: 99%